Netizen Journalism on Instagram as Local Digital Media and Communication Dynamics in the @infobekasi Account - Mira Adita Widianti; Ariandi Putra; Vivitri Endah Andriani (COMMUSTY Journal of Communication Studies and Society, 2025)
This study examined the communication dynamics of netizen journalism within the Instagram account @infobekasi as a local digital media platform in Bekasi. The study was conducted to address the limited understanding of how local social media accounts mediate citizen participation, content curation, and information dissemination. A qualitative research design with a descriptive–interpretative approach was employed. Primary data were collected through documentation of Instagram content, including posts and audience interactions, and were analyzed inductively through data reduction and thematic categorization. The findings showed that @infobekasi functioned as a hybrid media platform that integrated citizen-generated content, administrative curation, and audience interaction. The account also served as a local digital early warning system by enabling rapid circulation and social verification of local information. The study concluded that netizen journalism on social media reflected the transformation of local media practices in the digital era.